Approaches to Treating Knee Osteoarthritis: Surgery vs. Non-Surgery Treatment - Czyżewski, Filip; Banyś, Filip; Bochen, Konrad; Dudek, Stanisław; Jasiński, Filip; Łukawski, Artur; Pasierb, Karolina; Szałajska, Julia; Wiak, Iga; Wojtach, Klaudia (Quality in Sport, 2024)
Introduction: Knee Osteoarthritis (KO) is a progressive, chronic disease that damage the joint cartilage of a knee and leads to a changes in a anatomy of the joint. Both surgical and non-surgical methods are used to treat the disease. In this study, we will compare the invasive vs non-invasive methods of KO treatment. Objectives: The review and presentation of the current state of knowledge on Treating Knee Osteoarthritis, comparing surgery vs non-surgery methods. Material and Methods: Review of the studies available on open access sources at PubMed, Google Scholar and National Library of Medicine. Conclusions: Surgery approach for the Knee Osteoarthritis treatment are more durable, have better pain relief and treat casually the OA. Similar effects cannot be reached by non-surgery methods yet. However, there is a big promise in future studies about non-surgery methods, which can also raise a Quality of Life significantly and even avoid or postpone an operation in some groups of patients.